Efeito da estimulação emocional sobre o processamento sensorial auditivo - Hernández, Laura Carolina Ahumada (2016)
Emotions are crucial for the survivor of the organisms. They allow individuals to recognize what is threatening and what is safe in the environment. Emotions work modulating several cognitive processes, such as perception, attention and memory. At an electrophysiological level, emotions influence the response of neuronal networks measured by Event-Related Potentials (ERP). It has been documented that pleasant and unpleasant pictures increase the amplitude of the visual ERP in the visual areas of the brain. However, little is known about how emotions affect the processing of stimuli of different sensory modalities. The aim of this work was to test how the International Affective Picture System (IAPS) may affect the ERP of an innocuous sound. For this purpose the auditory ERP of 36 healthy students was recorded while they were watching a stream of high arousal unpleasant, high arousal pleasant, neutral images or a white screen. Heart rate variability (HRV), subjective self-report and band frequency power were measured too. Results showed that subjective self-report of the pictures emotional property verified the emotional qualities of these pictures, but it was slightly different form the Brazilian standard scores. We also found a deceleration of the HRV during emotional pictures viewing, and this correlated with the subjective self-report. No effect from emotional valence on the auditory ERP was found, only an effect of the pictures when compared to the white screen condition. In the left hemisphere, band frequency power showed a increase of theta and alpha power in the first moment for the four conditions. In a second moment, there was a increase of the power of this two bands during emotional pictures presentation in the right hemisphere. And then, it was seen a decrease in the right hemisphere of theta band power during unpleasant picture viewing. Scores from the subjective self-report and HRV confirmed that IAPS are a good method to elicit and evaluate emotions, but is necessary to extend the Brazilian standardization to have a more reliable instrument. Findings in the auditory ERP suggest a division of attention between the two kind of stimulation. Finally, the increase in the theta and alpha band power, especially in the right hemisphere, throughout the temporal series suggest a specialization of right hemisphere in the processing of emotional information.